Characterization of Factors Influencing Dimensional and Geometric Errors in PolyJet Manufacturing of Cylindrical Features. (2015) - Beltrán, N.; Carriles, F.; Álvarez, B.J.; Blanco, D.; Rico, J.C.
Abstract: Additive Manufacturing (AM) capabilities are evolving to overcome the mere manufacturing of prototypes. There are several challenges that AM processes must face in order to achieve reliable industrial-level applications. Thereby, improving dimensional and geometrical quality of AM parts has turned to be a key issue. Research efforts should be conducted in order to improve part quality, with the purpose of achieving industrial-degree tolerances. This objective becomes more relevant when parts have been designed to provide fitting, like those involving Features of Size (FoS). Present work deals with the analysis of factors influencing the quality of cylindrical features, on parts that have been manufactured using the PolyJet process. The purpose is to establish the relative influence of three main characteristics (size, location and orientation of the part within the manufacturing tray) upon dimensional and geometrical quality of cylindrical features belonging to a family of parts.